A status study of science attitudes of elementary school teachers in Trinidad and Tobago - Fraser-Abder, Pamela; Shrigley, Robert L. (My University, 1980)
The purpose of this study was to investigate the science attitude to primary school teachers in Trinidad and Tobago. The effects of six variables were tested: 1) gender difference, 2) teaching level, 3) school type, 4) geographical location, 5) mathematics courses, and 6) science courses. The Science Attitude Scale for In-Service Elementary Teachers (Shrigley and Johnson, 1974) was administered to 880 subjects representing the total population of primary school teacher enrolled at six teacher training colleges in the 1977-1978 academic year. Results of the data analysis showed that: 1) male teachers appeared to have a more positive attitude than female teachers, 2) teachers of 11-year-olds had a better attitude than teachers of six-year-olds, 3) the type of school attended did not appear to affect the science attitude of teachers, 4) rural and suburban teachers had a significantly higher attitude mean score than urban teachers, 5) attendance at mathematics courses did not appear to affect attitudes, and 6) scores of teachers having science at primary and secondary levels were significantly higher than teachers having science in primary school only or those having no science courses.
DOI: 10.1002/sce.3730640509
Keywords: primary school teachers